DOI: 10.18174/459940
|View full text |Cite
|
Sign up to set email alerts
|

Farmers in the lead : Assessing effectiveness of participatory experimentation inTigray, Northern Ethiopia

Abstract: The study area 1.10 Thesis outline 2 Comparison of methods to identify crop productivity constraints in developing countries. A review 2.1 Introduction 2.2 Heuristic model and prototype methods 2.3 Different use of methodologies: a review 2.4 Comparing different methods for the identification of productivity constraints in Tigray 2.5 Discussion 2.6 Conclusion 3 Identifying crop productivity constraints and opportunities using Focus Group Discussions: A case study with farmers from Tigray 3.1 Introduction 3.2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 221 publications
2
1
0
Order By: Relevance
“…Patients reported multiple reasons for choosing the ED including pain control, the belief that they would be seen by a doctor quickly, referral by another healthcare provider, and a lack of other healthcare options. These findings are consistent with those from more developed settings [13,14]; however, one key difference is that almost half of patients in the current study reported coming to the ED because their primary care clinic was closed, and one-third reported having no other option for seeking care. These numbers are substantially higher than in more developed settings [12,14,23].…”
Section: Plos Global Public Healthsupporting
confidence: 89%
See 2 more Smart Citations
“…Patients reported multiple reasons for choosing the ED including pain control, the belief that they would be seen by a doctor quickly, referral by another healthcare provider, and a lack of other healthcare options. These findings are consistent with those from more developed settings [13,14]; however, one key difference is that almost half of patients in the current study reported coming to the ED because their primary care clinic was closed, and one-third reported having no other option for seeking care. These numbers are substantially higher than in more developed settings [12,14,23].…”
Section: Plos Global Public Healthsupporting
confidence: 89%
“…These findings are consistent with those from more developed settings [13,14]; however, one key difference is that almost half of patients in the current study reported coming to the ED because their primary care clinic was closed, and one-third reported having no other option for seeking care. These numbers are substantially higher than in more developed settings [12,14,23]. The reasons for these findings are likely multifactorial.…”
Section: Plos Global Public Healthsupporting
confidence: 89%
See 1 more Smart Citation